The Reality of Continuous Evaluation in the English Language Course in the Elementary Stage in Saudi Arabia - Algosairi, Mishal Abdullah; Albdour, Ahmad Hasan (Journal of Curriculum and Teaching Methodology, 2023)
The study aims at exploring the level of achieving goals of continuous evaluation in the English language course from teacher’ point of view. It also aimed to reveal the differences between teachers’ responses about achieving goals of continuous evaluation in the English language course in the elementary stage, which are attributed to the number of students in the class and number of years of teaching experience. To achieve the objectives of the research, the researcher used the descriptive survey approach, the questionnaire was adopted as a tool for collecting data, and it was applied to a sample consisting of 397 teachers. The results showed that teachers achieve the goals of continuous evaluation in a high degree, and there are statistically significant differences between the responses of English language teachers about the achievement of continuous evaluation of students according to the number of students in the class, that is, the more the number of students in the class increases, the more goals of the continuous evaluation are achieved, it also showed that There are no statistically significant differences between the responses of English language teachers about achieving the goals of continuous evaluation of students according to the number of years of teaching experience. The researcher recommended a number of recommendations, summed up in diversification of tests in different times, and engaging teachers in curriculum development.